Risk of Prenatal Pesticide Exposure to Anemia and Stunted Birth in Horticultural Areas of West Lampung Regency, Indonesia - Yushananta, Prayudhy; Ahyanti, Mei (International Journal of Occupational Safety and Health, 2024)
Introduction: The massive use of pesticides in horticultural agriculture has raised significant concerns about their effects on human health, including fetal growth. This study aims to evaluate the risk of prenatal pesticide exposure to anemia and stunted birth in a horticulture center in Lampung Province, Indonesia. Methods: The study followed the pregnancies of 100 participants, grouped into exposed (WF=50) and unexposed (WNF=50). This study observes work methods, working hours, and protection used. Cholinesterase, hemoglobin, energy and protein intake were also measured (three periods). Birth length measurements were made at all births. Chi-square and stratification tests were used to assess differences in proportions between groups. Calculation of Relative Risk (RR) with 95% CI was applied to assess the risk of exposure to the outcome. Results: The study found that most participants were aged 21-35 years (80.0%), low income (87.0%), and 28.0% of WF had never given birth. There is no difference in the energy and protein intake proportion between WF and WNF (p-value> 0.05). But significantly different in poisoning status (p-value = 0.002) and hemoglobin level (p-value = 0.008). The risk of anemia in WF with poisoning is 4.57 (2.24-9.35) times. Furthermore, the risk of having a stunted baby from WF with anemia is 10.63 (1.16-97.26) times. Conclusion: This study has proven that pesticide exposure is a risk factor for anemia that impacts stunting. Examination of pesticide poisoning, nutritional monitoring during pregnancy, and social safety nets are recommended.